Risks of prostate cancer and mortality in the city of Sharjah, United Arab Emirates - Al Shareef, Zainab; Al-Shahrabi, Rula; Saheb Sharif-Askari, Fatemeh; Alshamsi, Younis; Zarooni, Abdulqadir Al; AlKhayyal, Noura; Soliman, Sameh S. M.; Bendardaf, Riyad; Halwani, Rabih (Frontiers in Oncology, 2023)
Background: Prostatic hyperplasia (BPH) and prostate cancer (PCa) are common age-related diseases in men. According to World Health Organization (WHO), PCa is the second most common cancer among Emirati men. This study aimed to identify the risk factors associated with PCa and mortality in a cohort diagnosed with PCa between 2012 and 2021 in Sharjah, United Arab Emirates (UAE). Methods: The data collected in this retrospective case-control study included patient demographics and comorbidities, as well as PCa markers such as prostate-specific antigen (PSA), prostate volume, prostate-specific antigen density (PSAD), and Gleason scores. Risk factors for PCa were assessed using multivariate logistic regression analysis, and factors associated with all-cause mortality in PCa patients were evaluated using Cox-proportional hazard analysis. Results: Of the 192 cases analyzed in this study, 88 were diagnosed with PCa and 104 were diagnosed with BPH. Regarding risk factors for PCa, a higher risk of PCa was associated with age 65 or older (OR=2.76, 95% confidence interval (CI): 1.04-7.30; P=0.038) and serum PSAD greater than 0.1 ng/mL2 (OR=3.48, 95% CI:1.66-7.32; P=0.001), whereas being of UAE nationals (OR=0.40, 95% CI:0.18-0.88; P=0.029) were associated with lower risk of PCa, after adjusting for patient demographics and comorbidities. Moreover, regarding cancer markers, higher serum PSA level (P=0.003) and smaller prostate volume (P=0.028) were associated with a higher risk of PCa, after adjusting with patients' age and BMI. Additionally, a high-grade Gleason score was associated with an increased risk of all-cause mortality after adjusting for patient's age and BMI (hazard ratio, aHR= 2.3, 95% CI:1.3-4.1; P= 0.016). Conclusions: This study found that age 65 or older and serum PSAD greater than 0.1 ng/mL2 are risk factors for PCa, while UAE nationality is associated with a lower risk. PSAD may be a better screening marker for PCa compared to traditional markers such as PSA and prostate volume.